2015
DOI: 10.1016/j.beproc.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in spatial navigation and perception in human adolescents and emerging adults

Abstract: Males typically outperform females on spatial tasks, beginning early in life and continuing into adulthood. This study aimed to characterize age and sex differences in human spatial ability using a virtual Water Maze Task (vWMT), which is based on the classic Morris water maze spatial navigation task used in rodents. Performance on the vWMT and on a task assessing visuospatial perception, Mental Rotations Test (MRT), was examined in 33 adolescents and 39 emerging adults. For the vWMT, significant effects of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 85 publications
(97 reference statements)
2
29
1
3
Order By: Relevance
“…We note that virtual versions of the Morris water maze test have been developed and validated (e.g., [112]), and are being used to translate the Morris water maze test findings from preclinical (animal) to clinical (human) populations (reviewed in [113]). The virtual versions are computer-assisted navigation tasks that provide auditory feedback to a participant [112].…”
Section: Epidemiological Studies and A Proposed Neurotoxic Moa In Humansmentioning
confidence: 99%
“…We note that virtual versions of the Morris water maze test have been developed and validated (e.g., [112]), and are being used to translate the Morris water maze test findings from preclinical (animal) to clinical (human) populations (reviewed in [113]). The virtual versions are computer-assisted navigation tasks that provide auditory feedback to a participant [112].…”
Section: Epidemiological Studies and A Proposed Neurotoxic Moa In Humansmentioning
confidence: 99%
“…In humans, as early as infancy, children have the ability to localize spatial information based on the relationship between an event and environmental features [2,3]. Studies show that a significant improvement in the ability to process spatial and contextual information occurs in adolescence, the consequence of rapid structural and functional changes in the brain from childhood into adolescence [3]. Sex differences in performing spatial tasks have long been observed in humans, non-human primates and rodents [49], but the underlying mechanisms are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies report better allocentric navigational performance in males, including prepubertal children (Newhouse, et al, 2007), some using computer-simulated versions of the MWM (Astur, et al, 1998(Astur, et al, , 2004Burkitt, et al, 2007;Daugherty, et al, 2014;Driscoll, et al, 2005;Mueller, et al, 2008;Nowak, et al, 2014;Sneider, et al, 2015;van Gerven, et al, 2012;Woolley, et al, 2010) have found no sex differences in performance (Jacobs, et al, 1997(Jacobs, et al, , 1998Sneider, et al, 2011). It is possible that inclusion of a probe trial, where the platform is removed unbeknownst to the participants, may have increased sensitivity in detecting sex differences in these studies as a male advantage has been demonstrated previously in probe trials even in the absence of performance differences in invisible-target trials (Nowak, et al, 2014;Sneider, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in spatial navigation have been widely reported, with males performing better across a range of ages, including young adulthood (Astur, et al, 1998;Astur, Tropp, Sava, Constable, & Markus, 2004;Burkitt, Widman, & Saucier, 2007;Driscoll, Hamilton, Yeo, Brooks, & Sutherland, 2005;Mueller, Jackson, & Skelton, 2008;Nowak, Diamond, Land, & Moffat, 2014;Sneider, et al, 2015;van Gerven, Schneider, Wuitchik, & Skelton, 2012;Woolley, et al, 2010), older adulthood (Driscoll, et al, 2005), prepubertal childhood (Newhouse, Newhouse, & Astur, 2007), and adolescence (Sneider, et al, 2015). Notably, some fMRI studies have shown differences in brain activation between males and females during spatial navigation (Grön, et al, 2000;Wunderlich, 2001), even in the absence of performance differences (Sneider, Sava, Rogowska, & Yurgelun-Todd, 2011).…”
Section: Introductionmentioning
confidence: 99%